2019
DOI: 10.1002/uog.20277
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in gynecological disease (16): clinical and ultrasound characteristics of serous cystadenofibromas in adnexa

Abstract: Objective To describe the clinical and ultrasound characteristics of serous cystadenofibromas in the adnexa. Methods This was a retrospective study of patients identified in the International Ovarian Tumor Analysis (IOTA) database, who had a histological diagnosis of serous cystadenofibroma and had undergone preoperative ultrasound examination by an experienced ultrasound examiner, between 1999 and 2012. In the IOTA database, which contains data collected prospectively, the tumors were described using the term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…Because of the low malignancy rate (2%) in this subgroup, the confidence interval around the AUC was wide. Calibration analysis indicated that the risk of malignancy was overestimated in this subgroup (supplementary figs[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The results obtained in the sensitivity analyses were similar to those in the primary analysis (supplementary figs[35][36][37][38][39][40][41][42][43].…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…Because of the low malignancy rate (2%) in this subgroup, the confidence interval around the AUC was wide. Calibration analysis indicated that the risk of malignancy was overestimated in this subgroup (supplementary figs[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The results obtained in the sensitivity analyses were similar to those in the primary analysis (supplementary figs[35][36][37][38][39][40][41][42][43].…”
mentioning
confidence: 54%
“…Most masses managed conservatively probably manifested clearly benign ultrasound signs, few were malignant, and most malignancies managed conservatively were borderline tumours, with ultrasound features that could be confused with those of benign tumours. 31 32 All models overestimated the risk of malignancy in patients who were managed conservatively, which was expected because none of the models was developed for this population.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, their size has been reported up to 30 cm, with an average diameter of 5-8 cm. 4 These neoplasms are complex, yet predominantly cystic. 5 The cysts are thin walled with a shiny exterior and are filled with clear, watery fluid or thin mucoid material.…”
Section: Discussionmentioning
confidence: 99%
“…To be considered a papillary projection, its height must measure at least 3 mm. 4 The second most common pattern of serous cystadenofibromas was discovered to be a multiloculated cyst that did not contain papillary projections, but did have small, solid internal components. Although less common, the third presentation was determined to be bilocular or multilocular cysts, and the fourth was a unilocular cyst.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation